Análise da imunoexpressão de proteínas relacionadas à autofagia (Atg7, LC3A, p62 e p-mTOR) em neoplasias de glândulas salivares - Pires, Emanuene Galdino (2020)
Pleomorphic adenoma (PA), polymorphous adenocarcinoma (PAC), mucoepidermoid carcinoma (MEC) and adenoid cystic carcinoma (ACC) are salivary gland neoplasms that exhibit important differences in their etiopathogenesis, histopathological characteristics and clinical behaviors. In the context of neoplastic development and progression, studies have highlighted the participation of an intracellular catabolic mechanism involved in physiological and pathological processes, denominated autophagy. This mechanism involves several molecules, with emphasis on Atg7, LC3, p62 and p-mTOR proteins. Investigations on autophagy in salivary gland neoplasms are recent and directed, especially, at ACC. In addition, these studies analyzed a small number of autophagy-related proteins, with emphasis on LC3 and mTOR. Thus, the objective of this study was to evaluate the immunoexpression of four autophagy-related proteins (Atg7, LC3A, p62 and p-mTOR) in PAs, PACs, MECs and ACCs of salivary glands. The sample consisted of 20 PAs, 20 PACs, 20 MECs and 14 ACCs. In the morphological study, the histopathological subtypes of PAs (cell-rich and cell-poor) (SOARES et al., 2009) and ACCs (cribriform, tubular and solid) (ELLIS; AUCLAIR, 2008) were analyzed. According to the histopathological grade of malignancy, MECs were classified as: grade I, grade II and grade III (BRANDWEIN et al., 2001). In the immunohistochemical study, the percentages of positive neoplastic cells (cytoplasm and nucleus) in 5 fields of highest immunoreactivity (400) for anti-Atg7, anti-LC3A, anti-p62 and anti-p-mTOR antibodies were determined (OUYANG et al., 2017). The data obtained were statistically analyzed using the Mann-Whitney test and Spearman’s correlation test (p < 0.05). There was a higher frequency of cell-rich PAs (60.0%) and cribriform (42.85%) and tubular (42.85%) ACCs. Regarding the histopathological grade of malignancy of MECs, there was a predominance of cases with grade I (45.0%) and grade II (45.0%). Cytoplasmic expression of Atg7 was observed in all groups analyzed, with high median percentages of positivity. For LC3A, cytoplasmic immunopositivity was found in most PACs (95.0%) and in all cases of PA, MEC and ACC. Regarding p62, the lowest percentages of cytoplasmic expression were observed in PAs and ACCs, both with significant difference compared to PACs and MECs (p < 0.05). The highest percentages of nuclear expression of p62 were observed in PAs, with statistically significant difference compared to PACs and ACCs (p < 0.005). ACCs showed lower percentages of cytoplasmic positivity for p-mTOR compared to other groups of lesions (p < 0.005). Regarding nuclear expression of Atg7, LC3A and p-mTOR, all groups exhibited low median percentages of positivity. There were no statistically significant differences in the immunoexpression of autophagy-related proteins according to the histopathological subtypes of PAs and ACCs and the histopathological grade of malignancy of MECs. In PAs, MECs and ACCs, positive correlations were observed between the immunoexpressions of autophagy-related proteins (p < 0.05). In conclusion, the results of this study suggest the potential involvement of autophagy in the pathogenesis of PA, PAC, CME and ACC of salivary glands. The upregulation of autophagy and the reduced nuclear translocation of protein p62 may contribute to aggressive biological behavior of ACC of salivary glands.